Pelatihan e-Faktur Sebagai Upaya Peningkatan Kompetensi Perpajakan Peserta Didik Lembaga Pendidikan Wearnes Malang - Yuniar Fitriyani (Madani : Indonesian Journal of Civil Society, 2023)
Tax experts are urgently needed since the Directorate General of Taxes has developed an information technology system to facilitate tax reporting, one of which is the e-Faktur application. The obstacle faced is the lack of prospective HR who are proficient in operating e-Faktur applications. Supporting the government program "Tax Goes To School", the target of training activities aimed at Wearnes Malang students as HR candidates so that they are well prepared to enter the world of work. The method used is dummy e-Faktur application workshops and tutorials. The evaluation results showed that the number of participants who were able to make accounting journals and calculate VAT correctly increased from 15 people before the training to 30 people after the training. While of the 30 participants who initially were not able to enter input taxes, output taxes, print invoices and make VAT returns, after the training all participants were able to enter input taxes, output taxes, print invoices and make VAT returns correctly using the e-Faktur application.